Suppression of mouse mammary tumor proviral DNA and protooncogene expression: association with nutritional regulation of mammary tumor development. - Chen, R F (1990)
Chronic energy intake restriction (CEIR) reduces mouse mammary tumor virus (MMTV)-induced mammary tumors in C3H/Ou mice. Fewer than 10% of C3H/Ou mice developed mammary tumors during 88 wk of study when subjected to CEIR regardless of calorie source (fat vs. carbohydrate). By contrast, 100% of mice fed ad libitum diets relatively high in fat or carbohydrate or a commercial diet developed tumors by 35-40 wk. MMTV proviral DNA transcription was shown to be activated in spleen, liver, lung, kidney, small intestine, and mammary gland of mice consuming these diets ad libitum. By contrast, these messages were suppressed by CEIR in all tissues analyzed except spleen. MMTV proviral messages in liver and mammary gland increased with age in full-fed mice and were suppressed by CEIR. These findings suggest that the nutritional regulation of MMTV proviral DNA expression is tissue-specific. In CEIR mice the suppressed MMTV proviral DNA transcripts in mammary gland and liver increased with time in association with the delayed onset of mammary tumors. Mammary tumorigenesis in C3H mice is associated with integration of MMTV proviral DNA, which appears to activate a putative mammary tumor protooncogene, int-1. CEIR apparently decreases the frequency of viral reintegration adjacent to the int-1 gene and thus inhibits expression of int-1 and probably an initiation step in mammary tumorigenesis. Expression of other putative protooncogenes, int-2 and ras, in liver tissue was also reduced by CEIR. These findings indicate that both initiation and promotion of mammary tumorigenesis are influenced by CEIR in C3H/Ou mice.